Review of learning materials of an ecology course at Universitas Terbuka - Yuni Tri Hewindati; Sri Kurniati Handayani; Aminudin Zuhairi; Raflen Aril Gerungan (AAOU Journal)
Purpose – This article presented the results of studies that examined the appropriateness of the content, readability of printed learning materials and the effectiveness of external resources in ecology course offered at Universitas Terbuka. To integrate external resources, links to their websites were provided in the printed materials. Design/methodology/approach – An in-depth interview with a content expert was employed to review the course content, while digital and printed learning materials were reviewed for readability and to determine the usefulness of the external resources. A total of 47 students completed surveys and a focus group discussion that included in-depth interviews were conducted with 21 selected students. Findings – The results revealed that the content of ecology course was conceptually valid. However, two key aspects needed to be emphasized, including the application of ecology phenomena for further development of the science and its applications in real-life situations. Regarding readability, students stated that the course materials were easily comprehended. In terms of the benefit, 79% of the students found the external resources interesting and helpful in understanding the learning materials. Practical implications – Printed learning materials were crucial for students, specifically those residing in remote areas. Therefore, the institution should ensure that the materials were high-quality, easy to comprehend and enriched with up-to-date content/materials through scannable links to external resources. Originality/value – The value added to the findings of this study was that the provision of links to external resources within printed learning materials improves students' understanding of the course content.